2020
DOI: 10.1111/twec.13013
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of real exchange rate volatility in South Africa

Abstract: Increasing financial liberalisation since the collapse of the Bretton Woods system in the 1970s has rendered exchange rates volatile in both developed and developing countries. As a result, the causes and effects of exchange rate volatility have become of interest to both researchers and policymakers. This paper focuses on the causes of medium to long-run real exchange rate volatility for South Africa's currency (the rand). This kind of study is important because medium to long-run real exchange rate volatilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Different statistical methods have been used in the literature to extract exchange-rate volatility. The present study used generalized autoregressive conditional heteroscedasticity (GARCH) and the moving standard deviation of exchange-rate times series to generate volatility, as widely documented in the literature (Khosa et al, 2015;Arize et al, 2000;Mpofu, 2016;Serenis & Tsounis, 2015;Musyoki et al, 2012). The following general expression is used:…”
Section: Estimating Exchange-rate Volatilitymentioning
confidence: 99%
“…Different statistical methods have been used in the literature to extract exchange-rate volatility. The present study used generalized autoregressive conditional heteroscedasticity (GARCH) and the moving standard deviation of exchange-rate times series to generate volatility, as widely documented in the literature (Khosa et al, 2015;Arize et al, 2000;Mpofu, 2016;Serenis & Tsounis, 2015;Musyoki et al, 2012). The following general expression is used:…”
Section: Estimating Exchange-rate Volatilitymentioning
confidence: 99%
“…Compared to the currencies of other emerging economies, the rand is more volatile as there is a highly developed foreign exchange market and high participation of foreigners in local markets. The country's good integration into the global economy could also be a factor in the volatility of the rand relative to other emerging economy currencies (Aye et al 2015;Hassan 2016;Khomo 2018;Mpofu 2016). This volatility of the exchange rate may have an effect on macroeconomic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Literature found that productivity determines the exchangerate volatility, but still empirically it proved different results. Productivity did not significantly affect exchange-rate volatility [9], while other researchers proved that productivity positively and significantly influences exchange-rate volatility [7], [8], and other proved that productivity negatively and significantly affected Exchange-rate volatility [10]. Government expenditure determines the exchange-rate volatility, but empirical results proved differently.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence still provides different evidence on money supply. Some significantly determines the exchange-rate volatility [28], and [10], however, some proved negative and not significantly determine the exchange-rate volatility [9], and [31]. Other factors according to the literature that affect exchange-rate volatility include: Interest rates, and exchange-rate regimes that positively and significantly affect the exchange-rate volatility [9], [7], [28].…”
Section: Introductionmentioning
confidence: 99%